2016
DOI: 10.1002/jeab.190
|View full text |Cite
|
Sign up to set email alerts
|

Complex conditional control by pigeons in a continuous virtual environment

Abstract: We tested two pigeons in a continuously streaming digital environment. Using animation software that constantly presented a dynamic, three-dimensional (3D) environment, the animals were tested with a conditional object identification task. The correct object at a given time depended on the virtual context currently streaming in front of the pigeon. Pigeons were required to accurately peck correct target objects in the environment for food reward, while suppressing any pecks to intermixed distractor objects whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Thus, perhaps not unsurprisingly, the pigeons took advantage of the entirety of the cues present in the displays. Being able to identify the specific contributions of these alternative cues provides greater confidence that the present results continue to point to the central role of global processing in the identification of the model’s behavioral movements (Cook & Roberts, 2007; Cook et al, 2001; Koban & Cook, 2009; Qadri et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, perhaps not unsurprisingly, the pigeons took advantage of the entirety of the cues present in the displays. Being able to identify the specific contributions of these alternative cues provides greater confidence that the present results continue to point to the central role of global processing in the identification of the model’s behavioral movements (Cook & Roberts, 2007; Cook et al, 2001; Koban & Cook, 2009; Qadri et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…With regards to the detection of the contributions of self-motion, they also have neurons that are sensitive to time to collision, again suggesting that motions relative to the self are critical (Wang & Frost, 1992). Behaviorally, Qadri et al (2016) found that pigeons could perform an object-based discrimination in a virtual environment where the approaching objects continually streamed by the central viewpoint, as if the animal was moving forward. These findings suggest that pigeons are likely sensitive to the motion and optic flow cues needed to account for changes in perspectives (see also Wylie et al, 1998).…”
mentioning
confidence: 99%
“…Occasion setting has been reported in a broad array of species, for example, humans (Baeyens et al, 2004), rats (Holland, 1992), mice (Shobe, Bakhurin, Claar, & Masmanidis, 2017), pigeons (Rescorla, 1985), honeybees (Giurfa & Menzel, 2003; Mota, Giurfa, & Sandoz, 2011), cockroaches (Matsumoto, Matsumoto, Watanabe, Nishino, & Mizunami, 2012), flies (Brembs & Weiner, 2006), and the nematode Caenorhabditis elegans (Law, Nuttley, & van der Kooy, 2004). It has been implicated in many conditioning phenomena that do not involve explicit occasion setting procedures, including the development of contextual control of behavior (“Context” section), renewal, reinstatement, relapse and spontaneous recovery after extinction (“Context” section), latent inhibition (Lubow & Gewirtz, 1995), conditioned inhibition (Rescorla, 1985, 1991a), avoidance learning (Declercq & De Houwer, 2008, 2009, 2011), and performance on sustained visual attention tasks (Hirsh & Burk, 2013; Qadri, Reid, & Cook, 2016; Schmajuk & Bushnell, 2009). Likewise, many types of commonly used conditional discrimination learning and memory tasks may substantially engage occasion-setting processes (Delamater et al, 2017; Holland, 1992).…”
Section: Implications Of Occasion Setting For Theories Of Associative...mentioning
confidence: 99%
“…They have also been tested with birds to examine perceptual grouping and texture segregation (Cook, 2001), motion detection and discrimination (Bischof et al, 1999), and the perception of Glass patterns (Nankoo et al, 2012;Qadri & Cook, 2015). Both physiological and behavioral studies have suggested that pigeons are sensitive to optic flow-like properties from these types of motion (Pakan & Wylie, 2006;Qadri et al, 2016;Wang et al, 1993;Wang & Frost, 1992;Wylie et al, 1998). Finally, a pilot test using action displays involving complex digital models had suggested that motion S/D discrimination might be challenging.…”
mentioning
confidence: 99%